Colombia - Development and Peace in the Magdalena Medio Region - Arboleda, Jairo; Garfield, Elsie (World Bank, Washington, DC, 2012)
The Program for Development and Peace in Magdalena Medio, supported by a Bank Learning and Innovation Loan, promotes a community-based participatory approach to development and peace in one of the most conflictive regions of Colombia. With a heavy emphasis on the strengthening of social capital and productive sub-projects, the Project offers important lessons on development interventions in conflict-affected regions.